MENINGKATKAN KETERAMPILAN MEMBUAT TEMPAT SENDOK DARI KALENG MELALUI METODE DEMONTRASI PADA ANAK TUNA GRAHITA RINGAN - Maidewilina - - (Jurnal Penelitian Pendidikan Khusus, 2014)
This research aims to determine the improvement of learning outcomes of sixth grade Lightweight Kids Tunagrahita SLB YAPEM Tarusan the subjects using the method of demonstration of skills. The data in this study were collected using a writing instrument and observation sheets. To see the changes in children's learning activities in two cycles ie cycles I and II. This involves writing class VI Kids Light Tunagrahita which amounts to 4 children. The data were obtained and analyzed using percentages. The findings indicate that the increase in writing skills children learning outcomes significantly. The results indicate that the results of the assessment of writing (early test) the ability of AD (10%), HR (20%), GR (10%) dan YS (20%). AD Cycle I got the results (60%), HR (50%), GR (70%) and YS scored (45%). In the second cycle the AD gets the value (90%), GR gets the value (85%), HR gets the value (95%) and YS scored (90%), this means that the method can improve the skills demonstration to make a place for children Tunagrahita Lightly spoon class VI in SLB YAPEM Tarusan.